A winter in California. - Wills, Mary H. (Norristown, Penna. [M.R. Wills], 1889)
Mary H. Wills left Norristown, Pennsylvania, to spend the winter of 1888-1889 in Southern California. A winter in California (1889) describes the highlights of her stay: visits to Pasadena, Los Angeles, Santa Barbara, Riverside, San Diego, Ojai Valley, Monterey, and Yosemite Valley. She shows special interest in climate, mission churches, shops, Chinatowns, hotels and restaurants. Her return rail journey allows a visit to Salt Lake City.
Also available in digital form on the Library of Congress Web site.
Keywords: California -- Description and travel; California, Southern -- Description and travel; Ethnic groups -- California; Women -- California; Urbanization -- California; Real estate development -- California; Religion and ethics -- California